2021
DOI: 10.1093/jbcr/irab142
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of Acupuncture on Pain Mechanisms, Inflammatory Responses, and Wound Healing in the Acute Phase of Major Burns: An Experimental Study on Rats

Abstract: Objectives We investigated acupuncture, a potential contributor for burn-care, on physiological and pathological pain mechanisms and systemic and local inflammatory responses in a rat experimental burn model. Methods Forty male Sprague-Dawley rats were divided into 2 groups. One-hour groups(5 rats/group) were observed for 1 hour and included Sh1(sham/observation), ShA1(sham+acupuncture/observation), Brn1(burn/observation), an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 40 publications
0
7
0
Order By: Relevance
“…However, animal experiments have suggested that acupuncture has the potential to mitigate pain, regulate inflammatory responses, and promote angiogenesis. [ 10 , 11 ] Previous studies on acupuncture point selection have primarily focused on acupoints located around or distal to the wound on the lower limbs, with no known instances of direct needling of the wound.…”
Section: Discussionmentioning
confidence: 99%
“…However, animal experiments have suggested that acupuncture has the potential to mitigate pain, regulate inflammatory responses, and promote angiogenesis. [ 10 , 11 ] Previous studies on acupuncture point selection have primarily focused on acupoints located around or distal to the wound on the lower limbs, with no known instances of direct needling of the wound.…”
Section: Discussionmentioning
confidence: 99%
“…Acupuncture is an important part of Chinese traditional medicine, and plays an important role in clinical treatment. Acupuncture can promote wound healing through anti‐inflammatory effects improving microcirculation, and increasing re‐epithelialization and angiogenesis 5,6 . Electrical stimulation is widely used as a physical stimulus in the medical field and is gaining more and more attention in the area of skin wound repair 7,8 .…”
Section: Introductionmentioning
confidence: 99%
“…Despite significant achievements in the field of regenerative medicine, cellular technologies and tissue engineering, the problem of adequate restoration of a full-fledged skin remains relevant in combustiology [1][2][3][4][5][6]. Therefore, it is advisable to search and evaluate the effectiveness of new ways to stimulate reparative regeneration of the skin after a burn [1,2,4].…”
Section: Introductionmentioning
confidence: 99%
“…Despite significant achievements in the field of regenerative medicine, cellular technologies and tissue engineering, the problem of adequate restoration of a full-fledged skin remains relevant in combustiology [1][2][3][4][5][6]. Therefore, it is advisable to search and evaluate the effectiveness of new ways to stimulate reparative regeneration of the skin after a burn [1,2,4]. At the same time, the multiplicity of technologies for local treatment of the burned significantly sidelines the elimination of the main cause of the formation and progression of burn disease-the burn wound itself [1,3,4,7].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation